TINJAUAN TERHADAP UPAYA PENANGKAPAN IKAN OLEH NELAYAN KECIL DI KABUPATEN PANGANDARAN BERDASARKAN UNDANG-UNDANG NOMOR 45 TAHUN 2009 - Xaverius Yodi Marbun; Sri Untari Indah Artati (Reformasi Hukum Trisakti, 2023)
The Minister of Maritime Affairs and Fisheries issued KKP Regulation No. 2/PERMEN-KP/2015 which prohibits the use of cantrang as a Fishing method for capture fisheries. As with the use of trawl in Pangandaran Regency in 2001 - 2019, it has increased by 2 times since foreign vessels can enter the region freely. The problems are 1) are Fishing efforts by small fisherman in Pangandaran Regency in accordance with Law No. 45 of 2009? and 2) what are the obstacles and how can the government resolve the law against small fishermen who catch fish using trawl in Pangandaran Regency based on KKP Regulation No. 18 of 2021. This study uses a descriptive approach to normative legal research. It involves a qualitative analysis of secondary data obtained from the study of literature and logical inference. The decision is as follows: 1) Article 9 paragraph (1) and (2) of Law No. 45 of 2009 on fisheries does not permit the use of cantrang as a common Fishing technique in Pangandaran Regency. 2) people feel that government efforts limit their well-being because the use of cantrang gives greater results.